Airway Hyperresponsiveness in Patients With Coronary Spastic Angina: Relationship Between Coronary Spasticity and Airway Responsiveness - Hirosawa, Koshichiro; Uchida, Tatsuro; Haruta, Shoji; Okayama, Michiko; Kasanuki, Hiroshi (Circulation Journal, 2007)
Background Several reports have suggested a possible link between bronchial asthma and coronary spasm, but the possibility of a relationship in coronary spastic angina (CSA) has not been clarified. Methods and Results Airway responsiveness to methacholine and coronary spasticity to acetylcholine were examined in 42 patients with CSA and 36 patients with chest pain syndrome (CP). Furthermore, 18 control subjects were examined and their airway responsiveness compared with that of the CSA and CP patients. The incidence of airway hyperresponsiveness was significantly higher in the CSA group (74%) than in the CP (19%) and control (17%) groups (p<0.0001). The geometric mean of the log minimum dose (Dmin), defined as the cumulative dose at the point at which respiratory conductance began to decrease, was significantly lower in the CSA group (0.75 log units) than in the CP (1.20 log units) and control (1.38 log units) groups (p=0.004). Conclusion These results demonstrate that acetylcholine-induced coronary spasticity is significantly related to methacholine-induced airway responsiveness in patients with CSA. A generalized hyperresponsiveness of the vascular and nonvascular smooth muscles, including that through cholinergic mechanisms, may exist in patients with CSA. (Circ J 2007; 71: 234 - 241)